Access Routes to BODY PART Multiword Expressions in the ’Big Five’ MELDs: Use of Hyperlinks - Wojciechowska, Sylwia (Lexikos, 2020)
The treatment of multiword expressions (MWEs) in dictionaries has not received much attention in metalexicography, although the significant role of phraseology has been stressed since the advent of corpus linguistics. The paper aims to analyse the lexicographic representation of semantically related MWEs, containing body part names. The study focuses on access routes to these MWEs in the ’Big Five’ monolingual English learners’ dictionaries online (MELDs). It investigates the presence and positions of hyperlinked MWEs on the page of the body part headword in order to find out if they depend on a given MWE or are dictionary-specific. Double or multiple hyperlinks to the same MWE are frequently found within a single body part entry, and the variety of access routes is evaluated with a view to offering a more homogeneous presentation of hyperlinked related MWEs.